Cu, N‐Codoped Carbon Nanodisks with Biomimic Stomata‐Like Interconnected Hierarchical Porous Topology as Efficient Electrocatalyst for Oxygen Reduction Reaction. Issue 43 (30th August 2019) - Wang, Tao; Yang, Rui; Shi, Naien; Yang, Jing; Yan, Hongyu; Wang, Junyi; Ding, Zhen; Huang, Wei; Luo, Qing; Lin, Yue; Gao, Jian; Han, Min
Abstract: Metal, N‐codoped carbon (M‐N‐C) nanostructures are promising electrocatalysts toward oxygen reduction reaction (ORR) or other gas‐involved energy electrocatalysis. Further creating pores into M‐N‐C nanostructures can increase their surface area, fully expose the active sites, and improve mass transfer and electrocatalytic efficiency. Nonetheless, it remains a challenge to fabricate M‐N‐C nanomaterials with both well‐defined morphology and hierarchical porous structures. Herein, high‐quality 2D Cu‐N‐C nanodisks (NDs) with biomimic stomata‐like interconnected hierarchical porous topology are synthesized via carbonization of Cu‐tetrapyridylporphyrin (TPyP)‐metal–organic frameworks (MOFs) precursors and followed by etching the carbonization product (Cu@Cu‐N‐C) along with re‐annealing treatment. Such hierarchical porous Cu‐N‐C NDs possess high specific surface area (293 m 2 g −1 ) and more exposed Cu single‐atom sites, different from their counterparts (Cu@Cu‐N‐C) and pure N‐C control catalysts. Electrochemical tests in alkaline media reveal that they can efficiently catalyze ORR with a half‐wave potential of 0.85 V (vs reversible hydrogen electrode), comparable to Pt/C and outperforming Cu@Cu‐N‐C, N‐C, Cu‐TPyP‐MOFs, and most other reported M‐N‐C catalysts. Moreover, their stability and methanol‐tolerant capability exceed Pt/C. This work may shed some light on optimizing 2D M‐N‐C nanostructures through bio‐inspired pore structure engineering, and accelerate their applications in fuel cells, artificial photosynthesis, or other advanced technological fields. Abstract : 2D Cu, N‐codoped carbon (Cu‐N‐C) nanodisks with stomata‐like interconnected hierarchical porous topology are fabricated by etching Cu‐tetrapyridylporphyrin(TPyP)‐metal–organic frameworks (MOFs) carbonization product (Cu@Cu‐N‐C) along with re‐annealing treatment. Due to their unique porous structures and fully exposed Cu single‐atom sites, such Cu‐N‐C nanodisks manifest exceptional electrocatalytic performance toward oxygen reduction, outperforming Cu@Cu‐N‐C, Cu‐TPyP‐MOFs, Pt/C, and most of other reported metal‐N‐codoped carbon catalysts.